Analisis Miskonsepsi Siswa Kelas IV Sekolah Dasar pada Pembelajaran Matematika Materi Bangun Datar Segi Empat: Kajian Literatur - Selvia Elpitri; Sukma, Elfia; Kharisma, Inggria (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to identify the types of misconceptions experienced by fourth-grade elementary school students regarding quadrilaterals through a literature review approach. This is a qualitative descriptive study using a literature review approach (library research). The data analysis technique employed is the Miles and Huberman interactive analysis model, which includes the stages of data reduction, data presentation, and drawing conclusions. The data sources consist of articles from national scientific journals obtained through searches of the electronic databases Google Scholar, ResearchGate, and SINTA. The results of the study indicate three main types of misconceptions consistently found among students, namely misconceptions regarding the position of quadrilaterals (classificational misconceptions), misconceptions regarding the terminology of quadrilaterals (theoretical misconceptions), and misconceptions regarding the relationships between quadrilateral shapes (correlational misconceptions). These three types of misconceptions stem from a lack of variety in the presentation of material, learning habits that rely on rote memorization, and students’ weak prior knowledge. Therefore, appropriate and comprehensive intervention is needed through a cognitive conflict approach, the use of diverse learning media, and the use of concept maps to ensure that misconceptions do not become obstacles to the development of students’ mathematical understanding in subsequent educational levels.